60.9k views
3 votes
Find the missing endpoint if S is the midpoint RT

S(-4,-6) and T (-7,-3) Find R

1 Answer

2 votes

Answer:

R(-1 , -9)

Explanation:

using Midpoint formula :-

(x1 + x2/2 , y1 + y2/2)

x1 + x2/2 = x( of midpoint)

x1 + -7( of T)/2 = -4 ( of S 'Midpoint')

x1 + -7 = -8

x1 = -1

y1 + y2/2 = y

y1 + -3/2 = -6

y1 + -3 = -12

y1 = -9

Therfore , R(-1 , -9)

User MTroy
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.